The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/adfm.201800653
|View full text |Cite
|
Sign up to set email alerts
|

A Transparent Membrane for Active Noise Cancelation

Abstract: This paper describes a method for active noise cancellation that uses an optically transparent membrane. The membrane consists of a prestretched hydrophobic elastomer, attached to a rigid frame, and sandwiched between two hydrogels swollen with an aqueous solution of salt.The elastomer functions as a dielectric, and the hydrogel functions as an ionic conductor. When the two hydrogels are subjected to a sinusoidal voltage, the membrane generates sound. A linear model for the reflection, transmission, and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The dynamic performance and the resonance of DEAs have been characterized both theoretically and experimentally using configurations such as pressurized DE balloons [7] [8], a DE minimum energy structure [9], spot DEAs [10] [11] [12], and pure shear DEAs [13] [14] [15]. The resonant actuation principle of DEAs has also been demonstrated in recent studies including vibrational crawling robots [16] [17], a rapid de-adhesion mechanism [18], a pneumatic pump [19] [20].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic performance and the resonance of DEAs have been characterized both theoretically and experimentally using configurations such as pressurized DE balloons [7] [8], a DE minimum energy structure [9], spot DEAs [10] [11] [12], and pure shear DEAs [13] [14] [15]. The resonant actuation principle of DEAs has also been demonstrated in recent studies including vibrational crawling robots [16] [17], a rapid de-adhesion mechanism [18], a pneumatic pump [19] [20].…”
Section: Introductionmentioning
confidence: 99%
“…Frame‐mounted DEA membranes and membrane stacks are geometries often explored as actuator types due to their conferral of prestrain into the materials. Evident in Figure 8c, Rothemund et al have reported the use of commercial DEAs integrated with stretchable, transparent ionic conductors based on polyacrylamide hydrogel with NaCl electrolyte for noise cancellation devices (Figure 8d) 160. This work is an extension from the fabrication of a transparent speaker (from DEA by Keplinger et al) 161.…”
Section: Dielectric Elastomersmentioning
confidence: 75%
“…Encapsulation of carbon grease electrodes has been described by La and Lau as a method to improve the contact and thermal stability of carbon grease electrodes 158. Optically transparent electrodes have also been a topic of interest, most notably the use of ionogels 159–161…”
Section: Dielectric Elastomersmentioning
confidence: 99%
See 1 more Smart Citation
“…The matrix was adapted to stick on the skin of a patient and transmitted signals between the skin and an electrode conductor supported by the base of the tray [ 22 ]. Philipp reported a pre-stretched hydrophobic elastomer that was sandwiched between two hydrogels, which functioned as ionic conductors to fabricate active noise cancelation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%